Teaching strategies : a guide to better instruction (Boston, Mass. : Houghton Mifflin, 2001)
A framework for instructional decisions. Fundamental tools for instructional planning. Instruction as a Dynamic process in classrooms.
Keywords: Education; Teaching; Teaching; Educational tests and measurements; Classroom management; Lesson planning